Crystallization: The Crystallization of PEDOT:PSS Polymeric Electrodes Probed In Situ during Printing (Adv. Mater. 22/2015). (June 2015) - Palumbiny, Claudia M.; Liu, Feng; Russell, Thomas P.; Hexemer, Alexander; Wang, Cheng; Müller‐Buschbaum, Peter
<x xml:space="preserve">Abstract</x> Organic electronics have emerged into a highly interesting field of research with a great variety of applications. On page 3391, P. Müller‐Buschbaum and co‐workers demonstrate the importance of in situ investigations during the printing process of organic electronics. In situ grazing‐incidence wide‐angle X‐ray scattering is used to follow the crystallization process of highly conductive PEDOT:PSS polymer mixtures. These findings are important for tuning transparent polymeric electrodes for organic electronics. Cover Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).